Job Demands and Service Performance in Hotel Front Office Operations: The Mediating Role of Employee Satisfaction - Wanti Arum Wanti; Ananta Budhi Danurdara; Nor Ismawanto Choirudin; Rudy Parlindungan Siahaan (AIBPM Publisher, 2025)
Hotel front office employees operate in high-contact service environments where workload, time pressure, and continuous guest interaction generate substantial job demands, making service performance a critical operational concern. This study examines the effect of job demands on service performance, with employee satisfaction as a mediating variable. Drawing on the Job Demands–Resources (JD-R) perspective, a quantitative survey was conducted among 200 front office employees in star-rated hotels in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct and indirect relationships among the constructs. The results show that job demands have a significant negative effect on both employee satisfaction and service performance. In addition, employee satisfaction partially mediates the relationship between job demands and service performance. These findings indicate that service performance is shaped not only by operational pressures but also by employees’ attitudinal responses to demanding work conditions. This study contributes by contextualizing job demands within front office operations and clarifying the mechanism through which operational pressure is translated into service outcomes. Practically, the findings highlight the importance of managing workload and sustaining employee satisfaction.